Knowledge and attitudes of Peruvian dental students toward caring for people with HIV/AIDS - Freddy Ronald Valdez Jurado; Mariaelena Moscoso Sanchez (Revista Cubana de Estomatología, 2022)
Introduction: To the WHO, education is an important strategy in the fight against HIV/AIDS. The Organization recommends that emphasis is made on the training of health professionals in the comprehensive management of the people affected with quality, ethics and dignity.